Handbook on mobile and ubiquitous computing : status and perspective - Yang, Laurence Tianruo; Syukur, Evi.; Loke, Seng. (Boca Raton, FL .: CRC Press, 2013)
'Written for those familiar with the basics and active in the area of mobile and ubiquitous computing, this volume contains papers that aid in understanding key issues and problems being tackled in the field. This text illustrates the design, implementation, and deployment of mobile and ubiquitous systems, particularly on mobile and ubiquitous environments, concepts, modeling, database components, and wireless infrastructures. It discusses new trends towards intelligent systems that aim to create software systems and discusses sensory input and multimedia information. The chapters also cover security, privacy, and trust'--
Includes bibliographical references and index.
Keywords: Mobile computing -- Handbooks, manuals, etc; Ubiquitous computing -- Handbooks, manuals, etc